2013
DOI: 10.5600/mmrr.003.04.b01
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for Meaningful Use of Health Information Technology and Patient Centered Medical Home Recognition Survey Results

Abstract: Objective: Determine the factors that impactHIT use and MU readiness for community health centers (CHCs). Background: The HITECH Act allocates funds toMedicaid and Medicare providers to encourage the adoption of electronic health records (EHR), in an effort to improve health care quality and patient outcomes, and to reduce health care costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Given that the success rate for the Navigator calls was low (only 19 of 152 (12.5 %) patients targeted completed a FIT in the subsequent 3 months), our results suggest the benefits of outreach can be largely realized through simple methods that leverage EHR data. EHRs are now used by the majority of CHCs in the U.S., 13 and most have the ability to deliver the automated elements of the outreach intervention under study here. Unlike previous studies, ours occurred in a CHC with established point-of-care strategies to improve CRC screening, including performance feedback, financial incentives, and use of FIT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the success rate for the Navigator calls was low (only 19 of 152 (12.5 %) patients targeted completed a FIT in the subsequent 3 months), our results suggest the benefits of outreach can be largely realized through simple methods that leverage EHR data. EHRs are now used by the majority of CHCs in the U.S., 13 and most have the ability to deliver the automated elements of the outreach intervention under study here. Unlike previous studies, ours occurred in a CHC with established point-of-care strategies to improve CRC screening, including performance feedback, financial incentives, and use of FIT.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Expanded use of FOBT, a modality with fewer barriers, may be a viable approach to address CRC screening disparities, especially with single-sample fecal immunochemical tests (FIT), which do not require dietary restrictions. 13 Several randomized trials have reported that outreach with FOBT can improve CRC screening rates. [14][15][16][17][18][19][20] However, most were conducted in integrated health plans.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] However, fewer than half of health centers used electronic records systems in all sites in 2011, instead of a mix of electronic and paper records systems. 18,19 This study sought to answer the following questions. First, how did health center adoption and use of EHR systems change from 2010 (the year before the start of the incentives) to 2012 (the second year of incentive payments)?…”
mentioning
confidence: 99%
“…Five studies used a mixed-methods approach to collect EHR use data. 33,37,46,52,55 Quantitative data collection methods were most frequently used, and included surveys (n ¼ 21) administered by mail, phone, or the Internet. Five studies used electronic data extraction or reporting.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…Ten studies did not specify a setting, but included primary care physicians or practices in their analyses. Some specified a particular category of health organization, such as patientcentered medical homes (n ¼ 2), 31,46 small-to mediumsized practices (n ¼ 4), 33,40,45,56 and rural primary care practices (n ¼ 2). 22,54 The perspectives of the studies reviewed varied in whether they measured EHR use at the level of the practice/clinic (n ¼ 16) or at the level of the individual physician (n ¼ 15).…”
Section: Settingmentioning
confidence: 99%